2021
DOI: 10.1002/cben.202000009
|View full text |Cite
|
Sign up to set email alerts
|

FlavonoidC‐Glycosyltransferases: Function, Evolutionary Relationship, Catalytic Mechanism and Protein Engineering

Abstract: C‐glycosylflavonoids are polyphenolic phytochemicals that are ubiquitously distributed in the plant kingdom and confer a wealth of health‐promoting benefits to human body. These compounds harbor one or more sugar moieties that are attached to various regions of the flavonoid scaffold through rigid C–C glycosidic bonds. The diverse structures of C‐glycosylflavonoids are granted by the prominent reactions of flavonoid C‐glycosyltransferases (CGTs). This review gives an extensive overview of CGTs that are involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…To date, only a few classes of potential substrates, in particular flavonoids, and their respective UGTs have been functionally characterized in detail. 5,34 This lack of insight is also largely due to hundreds of UGT-encoding genes in most plant species 10,11 and their substrate promiscuity. 24,35…”
Section: Uridine-diphosphate Dependent Glycosyltransferases (Ugt) Fam...mentioning
confidence: 99%
“…To date, only a few classes of potential substrates, in particular flavonoids, and their respective UGTs have been functionally characterized in detail. 5,34 This lack of insight is also largely due to hundreds of UGT-encoding genes in most plant species 10,11 and their substrate promiscuity. 24,35…”
Section: Uridine-diphosphate Dependent Glycosyltransferases (Ugt) Fam...mentioning
confidence: 99%
“…Although a wealth of structural and biochemical information of UGTs has been reported, they are generally characterized by high chemo- and regioselectivity and stringent substrate specificity or promiscuous substrate specificity but poor chemo- and regioselectivity. This severely hindered their applications in the targeted synthesis of specific glycosides. For example, in 2019, it was reported that the substrate scope of known flavonoid 3- O -glycosyltransferases is narrow and that their chemo- and regioselectivities are suboptimal . In another GT study, a structural comparison between the O -glycosyltransferase LanGT2 and the C -glycosyltransferase GTS8Ac was made. , In this mechanistic study, the effect of a remote mutation on the total enzyme conformation was reported, while the reshaping of the binding pocket was not aimed for.…”
Section: Introductionmentioning
confidence: 99%
“…Flavones, a subclassification of flavonoids, had also been identified in the present study, such as isoorientin and isovitexin, which are described as C-glycosyl flavonoids and are found in different plants [ 78 ]. Flavones have a variety of functions for the plant defense mechanism, similar to flavonoids, including interactions between species like resistance to pathogens, symbiosis, protection against herbivory, and allelopathy [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%